(untitled) (Revista Electrónica REDINE, 2018)
This essay is a construct to generate intentionality free time focusing on the socialization process from the educational perspective of recreation specialists Lara state. This was done as a literature review, as well as some informal interviews with some experts in the recreation area with the intention of carrying out an analysis of the theoretical foundations that support these practices. The basic idea is to train the individual on the theoretical aspect of free time and then on the good use of it in physical and recreational activities that require you to improve the quality of life. At the conclusion of this essay are some final thoughts that emerged from the review that generate the construct allowed for free time focusing on the socialization process in educational.